Profile of hospital admissions for migraine and other headache syndromes in children and adolescents in Brazil between 2013 and 2023 - Piloni, Bianca; Almeida, Luan; Silva-Néto, Raimundo Pereira (Headache Medicine, 2024)
Introduction: Migraine is a chronic neurological disease, with a prevalence of 15.2% in Brazil. It is defined as an abnormal neurovascular reaction that occurs in a genetically vulnerable individual. Clinically manifests itself in recurrent episodes of headache associated with other symptoms, dependent on triggering factors. Objective: To describe the epidemiological profile of hospital admissions of children and adolescents for migraine and other headache disorders. Methods: This was a retrospective and descriptive epidemiological study carried out with data extracted from the Brazilian Unified Health System's Hospital Information System (SIH/SUS), indexed to the Department of Informatics of the Unified Health System (DATASUS). Hospital admissions were selected based on age groups, with an emphasis on children under nine years old and adolescents between 10 and 19 years old, residing in Brazil, between July 2013 and June 2023. Results: Of 93,821 hospital admissions, there were 16,149 hospitalizations (17.2%) of children and adolescents (62.5% women and 37.5% men) due to migraine and other headache disorders. There was a predominance of the age group between 15 and 19 years old (50.2%), with a higher number of cases in the Southeast region (35.9%) and of brown ethnicity (42.6%). Over 10 years, there was a progressive increase in the number of hospital admissions, reaching a peak in 2019 (1,925/16,149; 11.9%), followed by a decline in 2020 and increasing again in subsequent years. Twenty-four deaths were found (24/16,149; 0.1%), 13 men and 11 women, with a predominance in the age group of 15 to 19 years (45.8%), coming from the Northeast region (58.3 %) and of brown ethnicity (58.4%). Deaths occurred predominantly in the years 2022 and 2023 (46.6%). Conclusions: There is an increase in the number of hospital admissions of children and adolescents due to migraine and other headache disorders with a consequent increase in the number of deaths.